Theory-based mobile phone text messaging intervention for blood pressure control (TEXT4BP) among hypertensive patients in Nepal: study protocol for a feasibility randomised controlled trial - Buna Bhandari; Padmanesan Narasimhan; Abhinav Vaidya; Rohan Jayasuriya (BMJ Open)
Introduction Uncontrolled blood pressure is one of the main risk factors for cardiovascular disease and death in Low-income and middle-income countries. Improvements to medication adherence and lifestyle changes can be assisted by using mobile phone text messaging interventions. This study aims to test the feasibility and acceptability of a text messaging intervention for blood pressure control ‘(TEXT4BP)’, developed based on behavioural change theory to improve treatment adherence and lifestyle change among hypertensive patients in Nepal.Methods and analysis The TEXT4BP intervention will be tested using a two-arm parallel-group, unblinded, individually randomised controlled trial. This feasibility study would recruit 200 clinically diagnosed hypertensive patients aged 18–69 years, currently receiving blood pressure-lowering medication for more than 3 months, visiting a tertiary healthcare facility in Kathmandu, Nepal. A nested qualitative study will assess the acceptability of the short message service intervention. The intervention group will receive text messages containing information on hypertension, diet, medication and physical activity three times a week for 3 months. The control group will receive standard care. At baseline and 3 months, measures of medication adherence, salt intake, physical activity and blood pressure will be collected. Feasibility measures, such as differential rates of recruitment and attrition rates, will be calculated. Acceptability of text message interventions will be studied using usability measures and in-depth interviews among intervention group participants. This pilot study is not funded.Ethics and dissemination This study has received ethics approval from the University of New South Wales Human Research Ethics Committee B (HC190357), Nepal Health Research Council (302/2019) and Institutional Review Committee of Kathmandu Medical College and Teaching Hospital Kathmandu, Nepal (030520192). The findings of the study will be disseminated through peer-reviewed publications and conference presentations.Trial registration number ACTRN12619001213134.